the prospect of indonesian small and medium enterprises in facing the implementation of ASEAN Economic comunitty 2015 as regional economic intergration - Firdha Irmawanti (Universitas Muhammadiyah Yogyakarta, 2009)
the prospect of indonesian small and medium enterprises in facing the implementation of ASEAN Economic comunitty 2015 as regional economic intergration